2017
DOI: 10.1139/cjz-2016-0271
|View full text |Cite
|
Sign up to set email alerts
|

Systemic effects of a high saturated fat diet in grizzly bears (Ursus arctos horribilis)

Abstract: Food sources for North America's grizzly bear (Ursus arctos horribilis Ord, 1815) population have changed as habitats have fragmented, altering available resources and putting bears in contact with unnatural foods. Bears have evolved mechanisms to tolerate obesity, and do not develop adverse health consequences despite storing massive amounts of body fat. Captive adult grizzly bears were used to determine the effects of dietary fat on health. Group 1 was fed a diet high in polyunsaturated fatty acids (PUFA) wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…This phenomenon indicates that mechanisms underlying this might provide new sight into preventing or reversing emerging diseases in the turtles. Furthermore, the maintenance of physiological function could also get inspiration from the ways grizzly bears deal with hibernation and their fluctuating weight (Rivet et al, 2017). These implied that hibernating animal is a good experimental animal model for improving the present situation of turtles.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon indicates that mechanisms underlying this might provide new sight into preventing or reversing emerging diseases in the turtles. Furthermore, the maintenance of physiological function could also get inspiration from the ways grizzly bears deal with hibernation and their fluctuating weight (Rivet et al, 2017). These implied that hibernating animal is a good experimental animal model for improving the present situation of turtles.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, there is a strong relationship between the body fat percentages of bears and their survival and reproductive capacity during hibernation (López-Alfaro et al, 2013;Robbins, Meray, Fortin, & Lynne Nelson, 2012). In addition to behavioral adaptation, brown bears have acquired a suite of physiological adaptations facilitating adiposity while simultaneously remaining healthy (Rivet, Nelson, Vella, Jansen, & Robbins, 2017). Bears primarily gain lean mass, if any, during the spring season when their diets are higher in protein content (Hilderbrand et al, 1999;Swenson, Adamic, Huber, & Stokke, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, adiponectin regulates insulin resistance and fatty acid oxidation, which promote the breakdown of glucose and fatty acids consumed in the diet 67 . However, previous studies with captive grizzly bears showed that adiponectin serum concentrations were positively correlated with a high saturated fatty acid diet and percent body fat, and increased gradually throughout the active season and peak in mid-October, prior to hibernation 68 , 69 . Thus, adiponectin may serve a different physiologic process in bears compared to humans and appears to be correlated with high fatty diet.…”
Section: Discussionmentioning
confidence: 84%